2018
DOI: 10.1177/1367006918814375
|View full text |Cite
|
Sign up to set email alerts
|

Shared core meanings and shared associations in bilingual semantic memory: Evidence from research on implicit memory

Abstract: Aims and objectives/purpose/research questions: The degree of overlap across languages in bilingual semantic memory has been debated in the cognitive bilingual literature for decades. This paper focuses on theory and recent evidence addressing the questions of whether translation-equivalent words in a bilingual person’s two languages access common core-meaning representations and whether long-standing semantic/conceptual associations among words are language-general or language-specific. Design/methodology/app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…Various models have been developed to seek an answer (e.g., bilingual interactive activation model, Dijkstra and Van Heuven, 2002; inhibitory control model, Green, 1998;distributed feature model, Van Hell and De Groot, 1998;revised hierarchical model, Kroll and Stewart, 1994) and, despite differing in the exact nature of L1 and L2 representations, these models share a consensual view about two assumptions relevant for the present review. First, both languages access a shared conceptual system (Francis, 1999(Francis, , 2020Francis et al, 2019) and, second, associations between word forms and their concepts are stronger in L1 than in L2 (e.g., Gollan et al, 2008). To further elaborate on these ideas, the revised hierarchical model (RHM) 1 , referred above, will be considered.…”
Section: Two Languages In One Brainmentioning
confidence: 99%
“…Various models have been developed to seek an answer (e.g., bilingual interactive activation model, Dijkstra and Van Heuven, 2002; inhibitory control model, Green, 1998;distributed feature model, Van Hell and De Groot, 1998;revised hierarchical model, Kroll and Stewart, 1994) and, despite differing in the exact nature of L1 and L2 representations, these models share a consensual view about two assumptions relevant for the present review. First, both languages access a shared conceptual system (Francis, 1999(Francis, , 2020Francis et al, 2019) and, second, associations between word forms and their concepts are stronger in L1 than in L2 (e.g., Gollan et al, 2008). To further elaborate on these ideas, the revised hierarchical model (RHM) 1 , referred above, will be considered.…”
Section: Two Languages In One Brainmentioning
confidence: 99%
“…was a Norwegian-English bilingual patient, but she had emigrated to the United States when she was five years old and has since predominately spoken English, so her bilingualism is unlikely to have strongly affected her performance. Given the evidence favoring a shared conceptual store across languages in bilinguals (see Francis, 2018), a semantic deficit should have been detectable in S.E.…”
Section: Participantsmentioning
confidence: 99%
“…Picture naming was included as an example of perceptual processing in early studies (Wiggs and Martin, 1998). Subsequent research however, particularly using bilingual participants, suggests that picture naming can be decomposed into object identification and word production: object identification is assumed to be a perceptual process, whereas word production requires conceptual access (Francis and Sáenz, 2007;Francis et al, 2008; for review, see Francis, 2020). Factor analysis has also suggested that picture naming taps both perceptual and conceptual factors (Bruss and Mitchell, 2009).…”
Section: Rs In Fusiform Gyrus and Inferior Frontal Gyrusmentioning
confidence: 99%